Combination of Urachal and Omphalomesenteric Duct Remnant: A Rare Case Reports - Maker, Luh Putu Iin Indrayani; Manna, Johana Sensy Leni; Darmajaya, I Made (Majalah Patologi Indonesia, 2024)
Umbilical problems encountered in the pediatric population are often associated with retained umbilical cord structures or with failure of the umbilical ring to close at birth. This article reported a case of umbilical anomalies in 3-years old male, with a chief complaint of a lump on the umbilical area a urinary discharge from the umbilical since birth. Incidence of patent vitelointestinal duct (omphalomesenteric duct) varies from 1 in 5000-8000 while patent urachus are still rare, ranging from 1-2 per 100000. The combination of both anomalies is very rare, only 12 reported cases since 1898 until 2016. Ultrasound can play an important diagnostic role for these types of anomalies if performed by expert. In our case, the ultrasound was not able to confirm the diagnosis due to a lot of gas in the abdomen. Based on clinical data and histopathologic examination, the patient was diagnosed with combination of urachal and omphalomesenteric duct remnant.